2022
DOI: 10.2196/31272
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From the Resilience of Chinese Hospitals to the COVID-19 Pandemic: Scoping Review

Abstract: Background The SARS-CoV-2 pandemic has brought substantial strain on hospitals worldwide; however, although the success of China’s COVID-19 strategy has been attributed to the achievements of the government, public health officials, and the attitudes of the public, the resilience shown by China’s hospitals appears to have been a critical factor in their successful response to the pandemic. Objective This paper aims to determine the key findings, recomme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Lacking recognition from upper-level management and facing social stigmas from the public add to these stressors. Our findings largely correspond with results from other international studies on related topics, demonstrating how most experiences are shared on a global level 16–30…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Lacking recognition from upper-level management and facing social stigmas from the public add to these stressors. Our findings largely correspond with results from other international studies on related topics, demonstrating how most experiences are shared on a global level 16–30…”
Section: Discussionsupporting
confidence: 89%
“…This increases the need for more hospital personnel and readjustments of staff schedules to shorter shifts to ensure a safe work place. 20 21 We also found that some qualified nurses without professional infectious disease background or training were recruited from other wards to remedy staff shortages. Redeployment of staff without specific training may lead to absenteeism, especially once the crisis is over.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations